1979
DOI: 10.1002/pol.1979.170170120
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition of poly(butylene terephthalate)

Abstract: Detailed results of the overall thermal degradation of poly(butylene terephthalate) are reported. Laser microprobe analysis and dynamic mass spectrometric techniques were used to identify the primary volatile degradation products and initial pyrolysis reactions that control polymer degradation. A complex multistage decomposition mechanism was observed which involves two major reaction pathways. Initial degradation occurs by an ionic decomposition process that results in the evolution of tetrahydrofuran. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

1981
1981
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 10 publications
2
42
0
2
Order By: Relevance
“…8), it was revealed that the first gaseous products evolving through PBSu decomposition were tetrahydrofuran, 1,3-butadiene and succinic acid anhydride, detected along with water and CO or CO 2 during the first 3.5 and 7 min of retention respectively. Similar decomposition products, except succinic anhydride, were also View Article Online observed during decomposition of poly(butylene terephthalate) (PBT) and are due to the existence of 1,4-butylene glycol 37 while CO and CO 2 are due to the carboxyl end groups of polyesters. 38,39 At higher retention times allyl and diallyl compounds with characteristic vinyl groups and higher molecular weights were detected.…”
Section: Evaluation Of Evolved Gas Analysis By Gc-msmentioning
confidence: 63%
“…8), it was revealed that the first gaseous products evolving through PBSu decomposition were tetrahydrofuran, 1,3-butadiene and succinic acid anhydride, detected along with water and CO or CO 2 during the first 3.5 and 7 min of retention respectively. Similar decomposition products, except succinic anhydride, were also View Article Online observed during decomposition of poly(butylene terephthalate) (PBT) and are due to the existence of 1,4-butylene glycol 37 while CO and CO 2 are due to the carboxyl end groups of polyesters. 38,39 At higher retention times allyl and diallyl compounds with characteristic vinyl groups and higher molecular weights were detected.…”
Section: Evaluation Of Evolved Gas Analysis By Gc-msmentioning
confidence: 63%
“…Blends of oligoester with the commercial polystyrene did not present any shift on the melting or isotropization temperature. [11][12][13] . These results clearly indicate an extensive miscibility in the polystyrene amorphous phase, in the block copolymer or polymer blend.…”
Section: Resultsmentioning
confidence: 99%
“…The degradation proceeds by free radical mechanism after the primary breakage of the ester linkage of the terephthalic acid ( Figure 1). This mechanism involves a cyclic transition state with the hydrogen at the β position, followed by a chain rupture process in which vinyl ester groups and carboxylic acids are formed [11][12][13] (Figure 1). A second stage was reported to be the thermal scission of the mesogenic group with phenylenic residues formation.…”
Section: Introductionmentioning
confidence: 99%
“…Although decomposition seems to proceed as a single step (e.g., Figure 5 for PBST), different mechanisms are probably involved, as reported for PBT [27]. In this case, degradation started with an ionic decomposition process that results in the production of tetrahydrofuran.…”
Section: Thermal Properties Of Copolyesters and Nanocompositesmentioning
confidence: 96%
“…In this case, degradation started with an ionic decomposition process that results in the production of tetrahydrofuran. The subsequent process was associated with ester pyrolysis reactions that yield 1,3-butadiene at the beginning and finally produced aromatic species [27]. Thermal degradation of several poly(butylene succinate-co-butylene terephthalate)s has also been previously reported [28], indicating a single weight-loss step.…”
Section: Thermal Properties Of Copolyesters and Nanocompositesmentioning
confidence: 99%